Development of a post-project review process for Fresh N' Famous Foods Inc. Chowking Restaurant Systems Development Department. - Atotubo, Karol Mae I.; Talisayon, Dr. Serafin D. (Quezon City University of the Philippines Diliman, 2013)
A firm's performance is enabled by an organization's ability to create and use knowledge (Polyani, 1967). A learning organization skillfully creates, acquires, and transfers knowledge. It modifies its behaviour to reflect new knowledge and insights (Garvin, 1993). A successful learning organization is adaptive. It modifies routines, processes, structures, and cultures to maximize and draw on learning capabilities of its people (Stalk, Evans and Schulman, 1992). Knowledge pertains to the capacity to act or create effective action. In Chowking, the Restaurant Systems department is one that is rich in knowledge. It continuously creates new knowledge for the organization, particularly store operations, and modifies and enhances existing knowledge. The structure of the department is functional and matrix type. Deliverables come in short and long term - projects which may or may not involve other functional departments. Lessons learned from each and every project are abundant and significant for the department and the organization. Chowking RS is faced with the challenge of capturing and storing such knowledge gained so that it may be adapted to other projects and used for continuous improvement of business processes. As Talisayon, Pavia and Dy (2009) cite, knowledge management is good if it results to better performance, greater productivity, better learning and innovations, more revenues, faster growth and greater value creation. The barriers and gaps to implementing a Post-project review process in Chowking Restaurant Systems were identified, described, and assessed through an internal survey and informal interviews with the team. The top three barriers identified are "tacitness of process knowledge", "time constraints", and "poor internal communication". There were other barriers cited which were not included in the survey, such as, "lack of understanding on what PPR really is", "level of commitment and/or the willingness of team members to conduct PPRs - culture or mindset that PPRs are not needed, insignificant or irrelevant", "general schedules do not include the PPR", "application of lessons learned in PPRs are limited", "too much competition within the department", and "simultaneous projects". Post-project review processes were benchmarked and analyzed in terms of applicability and adaptability, taking into consideration how the barriers and gaps towards implementation of a Post-project review process can be addressed. The proposed Post-project review process for Chowking Restaurant Systems includes the level of effort required specific to the type of project handled by the team, as well as specific methods appropriate for each project type. The potential knowledge products, different tools and templates for the conduct of a Post-project review are also included. In addition, a Knowledge Management Pitch was recommended prior to the start of establishing a Post-project review process to ensure that the team understands and appreciates the importance of Post-project reviews. Lastly, it was recommended that the proposed Post-project review process be integrated with the entire project management cycle of Chowking Restaurant Systems. Recommendations for further study and improvement were also provided; among which include alignment of the Post-project review process to the Performance Management System; inclusion of desirable behaviours of project team members in the Performance Management System; addition of Knowledge Management competencies as key competencies of Restaurant Systems employees; a better documentation and storage system for the knowledge captured from projects; and further training on facilitation skills.
In partial fulfillment of the requirements in TM 299.
Thesis
Keywords: Project management; Fresh N' Famous Foods Inc; Chowking Restaurant Systems Development Department; Post project review process